Positive electrode active material and method for preparing the same
Patent Information
- Application Number
- CN202610528452.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2025-04-24
- Filing Date
- 2026-04-21
- Publication Date
- 2026-10-27
AI Technical Summary
[0009]根据一些示例实施方式的用于制备正电极活性物质的方法可在使制造成本降低或最小化的同时改善在芯颗粒的表面上的碳材料的包覆良率(包覆产率,包覆率,coatingyield),且可制备具有期望的或改善的导电性的正电极活性物质。
Smart Images

Figure CN122992015A_ABST
Abstract
Description
Technical Field
[0001] The active material for the positive electrode and its preparation method are disclosed. Background Technology
[0002] Portable information devices such as cellular phones, laptops, and smartphones typically use rechargeable lithium batteries with high energy density and portability as their power source. Recently, high-energy-density rechargeable lithium batteries have proven advantageous as a power source or energy storage source for hybrid or electric vehicles.
[0003] Various positive electrode active materials have been studied to realize rechargeable lithium batteries for the aforementioned applications. For example, lithium nickel-based oxides, lithium nickel manganese cobalt composite oxides, lithium nickel cobalt aluminum composite oxides, and lithium cobalt oxides are mainly used as positive electrode active materials. For example, in the context of the increasing demand for large-size, high-capacity, or high-energy-density rechargeable lithium batteries, it is advantageous to develop positive electrode active materials that exhibit the desired or improved conductivity. Summary of the Invention
[0004] Some example implementations include a positive electrode active material capable of improving conductivity and a method for preparing the positive electrode active material.
[0005] In some example embodiments, the positive electrode active material includes a core particle comprising a lithium cobalt-based composite oxide and a carbon coating layer on the surface of the core particle. The carbon coating layer comprises graphene with a layered structure having 2 to 50 layers, and the size of the graphene, as measured by electron microscopy images of the surface of the positive electrode active material, is less than about 1 μm.
[0006] In some example embodiments, the positive electrode active material includes: a core particle comprising a lithium cobalt-based composite oxide and a carbon coating layer on the surface of the core particle. The carbon coating layer comprises graphene having a layered structure of 2 to 50 layers, and the graphene comprising the carbon coating layer is included in an amount greater than or equal to about 0.1% by weight based on a total of 100% by weight of the positive electrode active material.
[0007] In some example embodiments, the method for preparing the positive electrode active material includes: (i) preparing (preparing) core particles comprising a lithium cobalt-based composite oxide, and (ii) having an average size (D) in the range of about 3 μm to about 25 μm. 50 Flake-like graphite is pulverized to prepare graphite with an average size (D) of less than about 1 μm. 50 (iii) the use of microparticle graphite (microparticle graphite) and the use of dry mixing of core particles and microparticle graphite (dry mixing) to obtain a positive electrode active material.
[0008] The positive electrode active material according to some example embodiments can exhibit low powder resistance and improved conductivity. Furthermore, a positive electrode including the aforementioned positive electrode active material and a rechargeable lithium battery can have improved energy density.
[0009] The method for preparing positive electrode active material according to some example embodiments can improve the coating yield (coating yield, coating percentage) of carbon material on the surface of core particles while reducing or minimizing manufacturing costs, and can prepare positive electrode active material with desired or improved conductivity. Attached Figure Description
[0010] Figures 1 to 4 A cross-sectional view of a rechargeable lithium battery according to some example embodiments is shown schematically.
[0011] Figure 5 This is a scanning electron microscope image of the surface of particulate graphite used during the manufacture of the positive electrode active material in Example 1.
[0012] Figure 6 This is a scanning electron microscope image of the surface of the flake graphite used during the manufacture of the positive electrode active material in Comparative Example 1.
[0013] Figure 7 This is a scanning electron microscope image of the surface of particulate graphite used during the manufacture of the positive electrode active material in Comparative Example 2.
[0014] Figure 8 This is a scanning electron microscope image of the surface of the positive electrode active material prepared in Example 1.
[0015] Figure 9 This is a scanning electron microscope image of the surface of the positive electrode active material prepared in Comparative Example 1.
[0016] Figure 10 This is a scanning electron microscope image of the surface of the positive electrode active material prepared in Comparative Example 2.
[0017] Figure 11 This is a transmission electron microscope image of the cross-section of the positive electrode active material prepared in Example 1. Detailed Implementation
[0018] Hereinafter, exemplary embodiments are described in detail so that those skilled in the art can readily implement them. However, this disclosure may be embodied in many different forms and is not to be construed as limited to the exemplary embodiments set forth herein.
[0019] The terminology used herein is for descriptive purposes only and is not intended to limit the scope of this disclosure. Unless the context clearly requires otherwise, singular expressions include plural expressions.
[0020] "The combination of its components" means mixtures, laminates, complexes, copolymers, alloys, blends, reaction products, etc.
[0021] It should be understood that terms such as “comprising,” “including,” or “having” are intended to indicate the presence of the features, quantities, steps, elements, or combinations thereof embodied, but do not preclude the possibility of the presence or addition of one or more other features, quantities, steps, elements, or combinations thereof.
[0022] In the accompanying drawings, for clarity, the thickness of layers, films, panels, regions, etc., may be exaggerated, and the same reference numerals denote the same elements throughout the specification. It should be understood that when an element such as a layer, film, region, or substrate is referred to as being "on" another element, the element may be directly on the other element, or there may be intermediate elements therein. Conversely, when an element is referred to as being "directly on" another element, there are no intermediate elements.
[0023] The term "layer" in this article includes not only the shape that forms on the entire surface when viewed from a plan view, but also the shape that forms on a portion of the surface.
[0024] The average particle size can be measured by methods known to those skilled in the art, such as by a particle size analyzer or by transmission electron microscopy (TEM) or scanning electron microscopy (SEM) images. Alternatively, the average particle size value can be obtained by measuring using dynamic light scattering, performing data analysis, counting the number of particles in each size range, and calculating the average particle size value based on the count. As used herein, unless otherwise defined, the average particle size (D) is... 50 The mean particle size (D) can mean the diameter of particles that have a cumulative volume of 50% in the particle size distribution. As used herein, unless otherwise defined, the mean particle size (D) 50 This means the diameter of particles that have a cumulative volume of 50% in a particle size distribution obtained by randomly measuring the size (diameter or length of the major axis) of about 20 particles in a scanning electron microscope image.
[0025] "Or" is not interpreted as having an exclusive meaning. For example, "A or B" is interpreted as including A, B, A+B, etc.
[0026] The term "metal" is interpreted as encompassing common metals, transition metals, and metalloids (semi-metals).
[0027] When the terms “about” or “substantially” are used in this specification with respect to numerical values, it is intended that the relevant numerical values include a tolerance of ±10% around the stated value. When a range is specified, the range includes all values within that range, such as an increment of 0.1%.
[0028] Positive electrode active material
[0029] According to some example embodiments, the positive electrode active material includes: a core particle comprising a lithium cobalt-based composite oxide and a carbon coating layer on the surface of the core particle. The carbon coating layer comprises graphene having a layered structure ranging from 2 to 50 layers, and the size of the graphene, as measured by electron microscopy images of the surface of the positive electrode active material, is less than about 1 μm.
[0030] Typically, during the manufacturing of the positive electrode, binders and conductive materials are added to improve the adhesion strength between the electrode plate and the positive electrode active material, as well as the conductivity of the positive electrode. However, as the amount of binder and conductive material used increases, the following challenge arises: the energy density of the battery decreases because the amount of positive electrode active material decreases. Since the positive electrode active material according to some example embodiments includes a carbon coating layer (the carbon coating layer comprises a layered graphene structure ranging from 2 to 50 layers), even with a small amount of carbon material, the carbon coating layer can coat the surface of the active material particles, thereby enhancing adhesion strength and conductivity. Therefore, even with the use of a small amount of binder and conductive material during the manufacturing of the positive electrode, high energy density and conductivity can be ensured. Furthermore, as the amount of binder and conductive material used in the manufacturing of the positive electrode decreases, the amount of positive electrode active material can increase, allowing rechargeable lithium batteries including the positive electrode active material to exhibit high capacity and high energy density characteristics.
[0031] For example, when using crystalline carbon materials with low dispersion to form a carbon coating layer, the following challenge may exist: due to the aggregation of carbon materials, it is difficult to uniformly form a carbon coating layer on the surface of the core particles. However, according to some example embodiments, the positive electrode active material can achieve a carbon coating layer with a thin and uniform or substantially uniform thickness by selecting a crystalline carbon material as the source material (source material) for the carbon coating layer as desired, and coating the crystalline carbon material under appropriate or desired conditions. The carbon coating layer has a layered structure exhibiting a dense crystalline structure and may include crystalline carbon formed in a two-dimensional plane on the surface of the core particles. Therefore, the resistance of the positive electrode active material is reduced, lithium ion insertion and extraction are more efficient, and ionic conductivity is improved because lithium ions diffuse along the layered structure. Furthermore, even if the positive electrode does not contain a single conductive material or contains a substantially small amount of conductive material, the positive electrode including the positive electrode active material exhibits desired or improved electronic conductivity. Moreover, even if the positive electrode contains a substantially small amount of binder, the positive electrode including such positive electrode active material can exhibit high adhesion strength to the electrode plate. Rechargeable lithium batteries including such positive electrodes can exhibit high capacity and energy density, and can improve overall electrochemical performance such as charge / discharge efficiency and rate characteristics.
[0032] For example, uniformly coating the surface of a core particle with crystalline carbon material, which serves as the source material for the carbon coating layer, can be challenging, resulting in coating properties that are not as desired, such as uneven coating, aggregation on the surface, or separation from the surface. Furthermore, existing coating methods exhibit low coating yields of carbon material on the surface of the core particle, thus presenting a challenge of limiting the improvement of the conductivity of the positive electrode active material. However, in the case of positive electrode active materials according to some example embodiments, by controlling the size of the carbon material as desired, the size of the graphene included in the carbon coating layer can be adjusted to improve the coating yield on the surface of the core particle. Therefore, even with a substantially small amount of carbon material, a carbon coating layer including a large amount (high amount) of graphene can be formed on the surface of the core particle, and the electrical conductivity of the positive electrode active material can be improved or maximized due to a further reduction in the powder resistance of the positive electrode active material.
[0033] For example, there are methods for inducing a carbon coating layer including graphene on the surface of the core particles of a positive electrode active material using graphene as a raw material. However, the coating process is complex or costly, thus limiting commercialization. There are also limitations in ensuring a carbon coating layer with a uniform or substantially uniform thickness on the surface of the core particles. Additionally, there are techniques for coating amorphous carbon on the surface of core particles, but uniform or substantially uniform coating is difficult, and there are limitations in increasing energy density while simultaneously increasing the electronic conductivity and reducing the resistance of the positive electrode. According to some example embodiments, the positive electrode active material introduces graphene as a carbon coating layer on the surface of the core particles in the form of a uniform or substantially uniform film with a thickness ranging from 2 to 50 atomic layers or from a few nanometers to tens of nanometers. Compared to coating amorphous carbon or other crystalline carbons, the positive electrode active material according to some example embodiments achieves higher electronic and ionic conductivity, increases energy density while reducing resistance, and achieves superior electrochemical performance. Furthermore, according to some example embodiments, the positive electrode active material can be applied using a dry coating method while using graphite as a low-cost material, and thus cost reduction is possible, processability is as desired, and it is beneficial for large-scale production.
[0034] The following describes in detail the configuration of the positive electrode active material according to some example embodiments.
[0035] Core Particles
[0036] The core particles comprise lithium-cobalt-based composite oxides. For example, the core particles may comprise lithium-cobalt-based composite oxides represented by Chemical Formula 1:
[0037] Chemical Formula 1:
[0038] Li a1 Co x1 M 1 y1 O 2-b1 X b1 .
[0039] In chemical formula 1, 0.9 ≤ a1 ≤ 1.8, 0.7 ≤ x1 ≤ 1, 0 ≤ y1 ≤ 0.3, 0.9 ≤ x1 + y1 ≤ 1.1, and 0 ≤ b1 ≤ 0.1, M 1 X is or includes one or more elements of Al, B, Ba, Ca, Ce, Cr, Cu, Fe, Mg, Mn, Mo, Ni, Se, Si, Sn, Sr, Ti, V, W, Y, Zn, and Zr, and X is or includes one or more elements of F, P, and S.
[0040] When the core particles include lithium cobalt-based composite oxides represented by chemical formula 1, high-voltage designs for rechargeable lithium batteries are possible, and the reliability and safety of rechargeable lithium batteries can be improved due to reduced gas generation at high voltages. Furthermore, battery resistance can be reduced or suppressed by leveraging synergistic effects in fast-charging systems.
[0041] The average particle size (D) of the core particles 50 The core particle size can range from about 1 μm to about 25 μm, from about 3 μm to about 22 μm, or from about 10 μm to about 18 μm. If the average particle size (D) of the core particles... 50 The above range is satisfied (when the average particle size of the core particles (D) is within the range specified above). 50 When the above range is met, the electrical conductivity of the positive electrode active material can be improved while simultaneously promoting its structural stability. Furthermore, the stability of the positive electrode slurry and the density of the electrode plate mixture (mixing density) in the positive electrode manufacturing process can be improved. For example, since the movement path of lithium ions to the surface of the positive electrode active material becomes longer, the formation of impurities on the surface of the positive electrode active material can be reduced or minimized. Therefore, problems that may occur due to surface impurities, such as reduced battery capacity, increased interface resistance due to interference with lithium ion movement, gas generation due to impurity decomposition, and consequently, battery expansion, can be reduced or prevented. As a result, the capacity characteristics, high-temperature stability, and charge / discharge characteristics of the rechargeable lithium battery including the aforementioned positive electrode active material can be improved. In this paper, the average particle size (D) of the core particles is... 50 The particle size distribution can be obtained by randomly selecting about 20 particles from the scanning electron microscope image of the core particles, measuring their particle size (diameter, major axis, or major axis length) to obtain the particle size distribution, and then taking the size of the particles with a cumulative volume of 50% of the particle size distribution as the average particle size.
[0042] Core particles may include an average particle size (D) in the range of about 8 μm to about 20 μm. 50 The first particle and having an average particle size (D) in the range of about 0.5 μm to about 6 μm. 50 The second particle is the first particle with a relatively large average particle size. For example, the first particle with a relatively large average particle size can be represented as a large particle, and the second particle with a relatively small average particle size can be represented as a small particle. Because the positive electrode active material layer includes both large and small particles, capacity and energy density can be improved or maximized, and long cycle life characteristics can be achieved.
[0043] The average particle size of the first particle (D) 50 The particle size can range from about 9 μm to about 20 μm, from about 10 μm to about 18 μm, or from about 12 μm to about 16 μm. In this paper, the average particle size (D) of the first particle is...50 The average particle size (D) can be obtained through the following methods. 50 ): Approximately 20 particles are randomly selected from the scanning electron microscope image of the first particle, and the particle size (diameter, major axis, or length of major axis) is measured to obtain the particle size distribution. Then, the size of the particles with a cumulative volume of 50% of the particle size distribution is taken as the average particle size.
[0044] The average particle size of the second particle (D) 50 The particle size can range from about 0.8 μm to about 6 μm, from about 1.0 μm to about 5.8 μm, or from about 1.0 μm to about 5.5 μm. In this paper, the average particle size (D) of the second particle is... 50 The average particle size (D) can be obtained through the following methods. 50 ): Approximately 20 particles were randomly selected from the scanning electron microscope image of the second particle, and the particle size (diameter, major axis, or length of major axis) was measured to obtain the particle size distribution. Then, the size of the particles with a cumulative volume of 50% of the particle size distribution was taken as the average particle size.
[0045] carbon coating
[0046] The carbon coating layer, located on the surface of the core particle, comprises a layered graphene structure ranging from 2 to 50 layers, with the graphene size measured by electron microscopy of the surface of the positive electrode active material being less than approximately 1 μm. This carbon coating layer ensures conductivity and adhesion strength to the electrode plate, even with the use of small amounts of binder and conductive material during positive electrode manufacturing. Furthermore, by reducing the amount of binder or conductive material used during positive electrode manufacturing, the amount of positive electrode active material can be increased, allowing the rechargeable lithium battery to exhibit high capacity and high energy density characteristics. For example, the carbon coating layer comprises crystalline carbon formed in a two-dimensional plane on the surface of the core particle and can have a thin and uniform or substantially uniform thickness. Additionally, the graphene in the carbon coating layer can have a layered structure exhibiting a dense crystalline structure. Therefore, the electronic conductivity of the positive electrode active material is improved, the interfacial resistance is reduced, lithium-ion insertion and extraction occur more efficiently, and ionic conductivity is improved as lithium ions diffuse along the layered structure. Furthermore, by controlling the size of graphene as desired, the coating yield on the surface of the core particles can be improved, and a carbon coating layer including a large amount of graphene can be provided on the surface of the core particles even using a substantially small amount of carbon material. Therefore, the electrical conductivity of the positive electrode active material can be improved or maximized because the powder resistance of the positive electrode active material is further reduced.
[0047] Layered structures ranging from 2 to 50 layers can be represented as layered structures of 2 to 50 atomic layers. As an example, the carbon coating layer can comprise graphene with layered structures of 2 to 48 layers, 5 to 45 layers, 7 to 40 layers, or 10 to 35 layers. The number of layers in the layered structure can be measured in high-resolution transmission electron microscopy (HR-TEM) images of the positive electrode active material particles.
[0048] The interlayer spacing (d) of the layered structure 002 The interlayer spacing (d) can be in the range of about 0.320 nm to about 0.350 nm, for example, about 0.325 nm to about 0.348 nm, about 0.328 nm to about 0.345 nm, or about 0.330 nm to about 0.342 nm. 002 ) satisfies the above range (when the interlayer spacing (d) of the layered structure 002 When the above range is met, the conductivity of the positive electrode active material can be further improved. In this paper, the interlayer spacing (d) 002 ) can be measured using methods known to those skilled in the art. For example, the interlayer spacing (d) of a layered structure 002 The peaks on the (002) plane can be obtained by X-ray diffraction (XRD) of the carbon coating layer, and then analyzed. In this paper, the (002) plane represents the range of 25.0° < 2θ < 27.0°, where 2θ represents the diffraction angle. For example, conventional procedures equipped in XRD equipment can be used as data processing and analysis procedures to subject the XRD measurement data to noise removal (baseline setting), etc. In addition, the peak profiles on the (002) plane can be fitted using conventional fitting functions such as Gaussian functions, Lorentz functions, etc. For example, the interlayer spacing (d) of the layered structure 002 This can be achieved by measuring the interlayer spacing (d) of microparticle graphite. 002 The method is used to represent the interlayer spacing (d) of particulate graphite. 002 The number of layers and the interlayer spacing (d) in a layered structure can be measured via XRD analysis of particulate graphite. 002 The thickness of the coating layer was determined as an average of measurements of the cross-section of the core particle at multiple randomly selected locations using HR-TEM. Note that the correlation between these parameters follows the physical properties of the graphene coating layer, where the total thickness of the coating layer is the product of the number of layers and the average interlayer spacing.
[0049] Graphene may have a Raman spectrum in the range of about 0.15 to about 0.50, and for example about 0.15 to about 0.45, about 0.18 to about 0.45, or about 0.20 to about 0.40 at 1350 cm⁻¹. -1 Nearby peak intensity (I) D) at 1580 cm -1 Nearby peak intensity (I) G The ratio of (I) D / I G If graphene's I... D / I G The value satisfies the above range (when the I of graphene) D / I G When the value meets the above range, the conductivity of the positive electrode active material can be improved or maximized. For example, a Raman spectrometer (e.g., ICRM7000 (Renishaw), etc.) can be used at a laser wavelength of approximately 632 nm and a wavelength of approximately 946 cm⁻¹. -1 The Raman spectra were measured under the condition of the lowest Raman shift. The peak intensity ratios described in this paper are derived from the values at approximately 946 cm⁻¹. -1 The peaks observed were obtained from the Raman shift range starting from the lowest Raman shift. These measurement conditions are standard in the art and the following are within the capabilities of those skilled in the art: adjusting these parameters, such as laser power or exposure time, while maintaining the relative trend of the peak intensity ratio to ensure reproducibility.
[0050] For example, the size of graphene can be less than or equal to about 0.9 μm, less than or equal to about 0.8 μm, less than or equal to about 0.7 μm, less than or equal to about 0.6 μm, or less than or equal to about 0.5 μm, and can be greater than or equal to about 0.01 μm, greater than or equal to about 0.05 μm, or greater than or equal to about 0.08 μm, and can be about 0.01 μm to about 0.8 μm, about 0.01 μm to about 0.6 μm, or about 0.05 μm to about 0.5 μm. If the size of graphene meets the above ranges (when the size of graphene meets the above ranges), a larger amount of graphene can be formed on the surface of the core particle with a uniform or substantially uniform thickness, and the conductivity of the positive electrode active material can be further improved because the powder resistance is further reduced. In this document, regarding the size of graphene, since graphene is sheet-shaped, it means the longest length or the length of the long axis in the portion corresponding to the surface of the sheet, rather than the thickness of the sheet. The size of graphene can be defined as the longest length of a line connecting one point on one surface of a graphene sheet to another. For example, the size of graphene can be measured by TEM (transmission electron microscopy), SEM (scanning electron microscopy), AFM (atomic force microscopy), TOF-SIMS (time-of-flight secondary ion mass spectrometry), XPS (X-ray photoelectron spectroscopy), or EDS (energy-dispersive spectroscopy), and, for example, by electron microscopic images of the surface of a positive electrode active material.
[0051] The size of graphene is related to the average particle size (D) of the core particles.50 The ratio of the graphene size to the average particle size (D) of the core particles can be less than about 0.1, and for example, can be less than or equal to about 0.09, less than or equal to about 0.08, less than or equal to about 0.07, less than or equal to about 0.06, or less than or equal to about 0.05, and can be greater than or equal to about 0.001, greater than or equal to about 0.005, greater than or equal to about 0.01, or greater than or equal to about 0.015. If the size of the graphene is relative to the average particle size (D) of the core particles... 50 The ratio of the graphene size to the average particle size (D) of the core particles satisfies the above range. 50 When the ratio of the two particles meets the above range, a larger amount of graphene can be formed on the surface of the core particles with a uniform or substantially uniform thickness, and the conductivity of the positive electrode active material can be further improved. Here, the average particle size (D) of the core particles... 50 The size of graphene can be measured using a particle size analyzer with laser diffraction, and the size of graphene can be measured using SEM images of the surface of the positive electrode active material particles.
[0052] The thickness of graphene can be less than or equal to about 20 nm. For example, the thickness of graphene can be less than or equal to about 19 nm, less than or equal to about 18 nm, less than or equal to about 17 nm, less than or equal to about 16 nm, or less than or equal to about 15 nm, and can be greater than or equal to about 1 nm, greater than or equal to about 2 nm, greater than or equal to about 3 nm, greater than or equal to about 4 nm, or greater than or equal to about 5 nm. If the thickness of graphene meets the above ranges (when the thickness of graphene meets the above ranges), a larger amount of graphene can be formed on the surface of the core particle with a uniform or substantially uniform thickness, and the conductivity of the positive electrode active material can be further improved. In this paper, the thickness of graphene can be measured by Raman spectroscopy. For example, it can be based on the Raman spectrum at 1580 cm⁻¹. -1 The peak intensity near 2700 cm⁻¹ -1 The thickness of graphene is measured by the ratio of nearby peak intensities. However, this disclosure is not limited to this, and the thickness of graphene can be measured by, for example, TEM, SEM, AFM, TOF-SIMS, XPS, or EDS analysis. As an example, the thickness of graphene can be measured by SEM or TEM images of the cross-section of the positive electrode active material particles.
[0053] The carbon-coated graphene can be derived from graphene with an average size of less than about 1 μm, as measured by a particle size analyzer using laser diffraction. 50The method involves using particulate graphite. In this case, due to the improved coating yield of particulate graphite, a larger amount of graphene can be formed on the surface of the core particles with a uniform or substantially uniform thickness, thus improving or maximizing the conductivity of the positive electrode active material. Furthermore, it improves the structural stability of the positive electrode active material, effectively reduces or suppresses side reactions with the electrolyte, reduces gas generation under high voltage and high temperature conditions, and achieves long cycle life characteristics.
[0054] Particulate graphite may be or include tabular particles. The average size (D) of particulate graphite 50 The average size of the particulate graphite can be less than about 1 μm, and for example, it can be less than or equal to about 0.9 μm, less than or equal to about 0.8 μm, less than or equal to about 0.7 μm, less than or equal to about 0.6 μm, or less than or equal to about 0.5 μm, and can be greater than or equal to about 0.01 μm, greater than or equal to about 0.05 μm, or greater than or equal to about 0.08 μm. If the average size of the particulate graphite meets the above range (when the average size of the particulate graphite meets the above range), because the coating yield of the particulate graphite is improved, a larger amount of graphene can be formed on the surface of the core particles with a uniform or substantially uniform thickness, and the conductivity of the positive electrode active material can be improved or maximized. Here, the average size of the particulate graphite (D 50 It can be measured using a particle size analyzer that employs laser diffraction, and it signifies the size of particles that constitute 50% of the total volume in the particle size distribution. Alternatively, particle size here can refer to the length of the longest axis in a plane perpendicular to the thickness direction within a plate shape.
[0055] The average size (D) of particulate graphite 50 The average particle size (D) of the core particles 50 The ratio can be less than 0.1, and for example, can be less than or equal to about 0.09, less than or equal to about 0.08, less than or equal to about 0.07, less than or equal to about 0.06, or less than or equal to about 0.05, and can be greater than or equal to about 0.001, greater than or equal to about 0.005, greater than or equal to about 0.01, or greater than or equal to about 0.015. If the average size of the particulate graphite (D...) 50 The average particle size (D) of the core particles 50 The ratio of ) satisfies the above range (when the average size of the particulate graphite (D) 50 The average particle size (D) of the core particles 50 When the ratio of the two components meets the above range, a larger amount of graphene can be formed on the surface of the core particles with a uniform or substantially uniform thickness, and the conductivity of the positive electrode active material can be further improved.
[0056] The thickness of the particulate graphite can be less than or equal to about 1.0 μm, and for example, less than or equal to about 1 μm, less than or equal to about 0.9 μm, less than or equal to about 0.7 μm, or less than or equal to about 0.5 μm, and can be greater than or equal to about 0.01 μm, greater than or equal to about 0.05 μm, or greater than or equal to about 0.08 μm. If the thickness of the particulate graphite meets the above ranges (when the thickness of the particulate graphite meets the above ranges), a larger amount of graphene can be formed on the surface of the core particles with a uniform or substantially uniform thickness because the coating yield of the particulate graphite is improved, and the conductivity of the positive electrode active material can be improved or maximized. In this paper, the thickness of the particulate graphite can be measured by transmission electron microscopy. Alternatively, the thickness of the particulate graphite can be measured by transmission electron microscopy of a cross-section of particulate graphite particles cut by FIB. However, this disclosure is not limited thereto, and the thickness of the particulate graphite can be measured by, for example, SEM, TEM, TOF-SIMS, XPS, AFM or EDS analysis, and / or by TEM-EDS line profile.
[0057] Particulate graphite may have a Raman spectroscopy value in the range of about 0.15 to about 0.50, for example about 0.15 to about 0.45, about 0.18 to about 0.45, or about 0.20 to about 0.40 at 1350 cm⁻¹. -1 Nearby peak intensity (I) D ) at 1580 cm -1 Nearby peak intensity (I) G The ratio of (I) D / I G If the I of particulate graphite D / I G The value satisfies the above range (when the I of particulate graphite) D / I G When the value meets the above range, a carbon coating layer with a uniform or substantially uniform thickness can be formed on the surface of the core particle, and the conductivity of the positive electrode active material can be improved or maximized.
[0058] Based on the total weight of 100% by weight of the positive electrode active material, the amount of graphene with a carbon coating may range from about 0.09% by weight to about 3.0% by weight, and for example, based on the total weight of 100% by weight of the positive electrode active material, the amount of graphene with a carbon coating may range from about 0.09% by weight to about 2.8% by weight, about 0.09% by weight to about 2.5% by weight, about 0.092% by weight to about 2.0% by weight, about 0.092% by weight to about 1.0% by weight, about 0.095% by weight to about 0.5% by weight, or about 0.095% by weight to about 0.8% by weight. If the amount of graphene meets the above range (when the amount of graphene meets the above range), by reducing the powder resistance of the positive electrode active material, the high capacity and high energy density characteristics of the rechargeable lithium battery can be improved while ensuring conductivity. For example, even when the amount of graphene is substantially small (less than about 1% by weight), it still coats the surface of the particles as desired to increase the electronic conductivity of the positive electrode active material, thereby increasing the electrical conductivity and density of the positive electrode. The amount of graphene can be measured using a CS analyzer, and for example, it can be measured by the method described in Evaluation Example 2 below.
[0059] For example, the carbon coating can be in the form of a film that continuously or substantially continuously surrounds the surface of the core particle, or it can be in the form of a shell that surrounds the entire surface of the core particle. This differs from structures where only a portion of the surface of the core particle is partially coated. When the carbon coating is provided in the form of completely surrounding the surface of the core particle, the conductivity of the positive electrode active material can be improved or maximized. Additionally, it can improve the electrode plate adhesion strength of the positive electrode active material, prevent an increase in resistance or a decrease in capacity, improve structural stability, effectively reduce or suppress side reactions with the electrolyte, reduce gas generation under high voltage and high temperature conditions, and achieve long-life characteristics.
[0060] The thickness of the carbon coating can be in the range of about 3 nm to about 50 nm, and for example, about 3 nm to about 45 nm, about 3 nm to about 40 nm, about 3 nm to about 35 nm, about 3 nm to about 30 nm, about 4 nm to about 20 nm, or about 5 nm to about 15 nm. If the thickness of the carbon coating meets the above range (when the thickness of the carbon coating meets the above range), the structural stability of the positive electrode active material can be improved, and side reactions with the electrolyte can be effectively reduced or suppressed without increasing resistance or decreasing capacity due to the carbon coating. For example, the thickness of the carbon coating can be measured by transmission electron microscopy of the cross-section of the positive electrode active material particles cut by focused ion beam (FIB). However, this disclosure is not limited thereto, and the thickness of the carbon coating can be measured by, for example, SEM, AFM, TOF-SIMS, XPS, or EDS analysis, and can be measured by TEM-EDS line profiling.
[0061] As an example, the carbon coating layer can have a uniform or substantially uniform thickness, while also being thin at the level of a few nanometers to tens of nanometers. For example, the difference between the highest and lowest thicknesses of the carbon coating layer can be less than or equal to about 30 nm, such as less than or equal to about 25 nm, less than or equal to about 20 nm, or less than or equal to about 15 nm, and can be greater than or equal to about 0.30 nm, greater than or equal to about 0.33 nm, greater than or equal to about 0.35 nm, or greater than or equal to about 0.40 nm. The fact that the difference between the highest and lowest thicknesses of the carbon coating layer meets the above-mentioned ranges means that a carbon coating layer of uniform or substantially uniform thickness can be formed as desired in the form of a film on the surface of the positive electrode active material particles, and therefore, the conductivity of the positive electrode active material can be improved or maximized. In this paper, the highest and lowest thicknesses of the carbon coating layer can be measured based on electron microscopy images of the positive electrode active material. For example, in an electron microscope image of the cross-section of a positive electrode active material particle, the thickness of the thickest part of the carbon coating can be defined as the maximum thickness of the carbon coating, and the thickness of the thinnest part can be defined as the minimum thickness of the carbon coating. The thickness of the carbon coating can be the vertical distance from the outer surface of the core particle to the outer surface of the carbon coating. For example, a scanning electron microscope or a transmission electron microscope can be used as the electron microscope.
[0062] For example, the powder resistivity of the positive electrode active material can be less than or equal to about 10,000 Ω·cm, less than or equal to about 9,000 Ω·cm, less than or equal to about 8,500 Ω·cm, or less than or equal to about 8,000 Ω·cm, and can be greater than or equal to about 100 Ω·cm, greater than or equal to about 500 Ω·cm, greater than or equal to about 1,000 Ω·cm, or greater than or equal to about 2,000 Ω·cm. The fact that the powder resistivity of the positive electrode active material meets the above ranges means that the conductivity of the positive electrode active material is exhibited as desired, and thus the electrochemical characteristics of the rechargeable lithium battery, such as capacity, initial efficiency, and cycle life characteristics, can be improved. For example, the powder resistivity of the positive electrode active material can be measured using a powder ohmmeter and can be expressed as the powder resistivity measured at 20 kN by applying pressure to the positive electrode active material particles in the range of 0 kN to 20 kN.
[0063] The positive electrode active material according to some example embodiments includes: a core particle comprising a lithium cobalt-based composite oxide; and a carbon coating layer on the surface of the core particle. The carbon coating layer comprises graphene having a layered structure ranging from 2 to 50 layers, with the graphene comprising the carbon coating layer in an amount greater than or equal to about 0.09% by weight based on 100% by weight of the total weight of the positive electrode active material.
[0064] In the case of positive electrode active materials, the coating yield on the surface of the core particles can be improved by controlling the size of the crystalline carbon material, which serves as the source material for the carbon coating layer, as desired. Therefore, even using a substantially small amount of carbon material, a carbon coating layer comprising a large amount of graphene can be formed on the surface of the core particles, and the electrical conductivity of the positive electrode active material can be improved or maximized due to a further reduction in the powder resistance of the positive electrode active material. For example, based on the total weight of 100% of the positive electrode active material, the amount of graphene included in the carbon coating layer can range from about 0.09% to about 2.8% by weight, 0.09% to 2.5% by weight, 0.092% to 2.0% by weight, 0.092% to 1.0% by weight, 0.095% to 0.5% by weight, or 0.095% to 0.8% by weight. If the amount of graphene meets the above-mentioned range (when the amount of graphene meets the above-mentioned range), the high capacity and high energy density characteristics of rechargeable lithium batteries can be improved while ensuring conductivity by reducing the powder resistance of the positive electrode active material. For example, even if the amount of graphene is a substantially small amount (less than about 1% by weight), graphene is still coated on the surface of the particles as desired to increase the electronic conductivity of the positive electrode active material, thereby increasing the electrical conductivity and density of the positive electrode.
[0065] The descriptions of the core particles and carbon coating of the positive electrode active material can be the same as those described above, and therefore their detailed descriptions are omitted.
[0066] Method for preparing positive electrode active materials
[0067] A method for preparing a positive electrode active material according to some example embodiments includes: (i) preparing core particles comprising a lithium cobalt-based composite oxide; (ii) having an average size (D) in the range of about 3 μm to about 25 μm. 50 Flake graphite was pulverized to prepare a material with an average size (D) of less than about 1 μm. 50 (iii) the use of particulate graphite; and (iii) the dry mixing of core particles and particulate graphite to obtain a positive electrode active material.
[0068] According to some exemplary embodiments, a method for preparing a positive electrode active material may use particulate graphite to form a carbon coating layer of graphene comprising a layered structure ranging from 2 to 50 layers on the surface of a core particle. Furthermore, the average size (D) of the particulate graphite is adjusted by controlling the pulverization conditions of the flake graphite. 50 This method improves the coating yield of particulate graphite on the surface of the core particles in step (iii) below, and even with a substantially small amount of particulate graphite, a carbon coating layer including a large amount of graphene can be formed on the surface of the core particles. Therefore, because the powder resistance of the positive electrode active material is further reduced, the electrical conductivity of the positive electrode active material can be improved or maximized. The method for preparing the positive electrode active material according to some example embodiments can prepare a positive electrode active material with high conductivity while reducing or minimizing manufacturing costs, and ensures conductivity and adhesion strength to the electrode plate even when a small amount of binder and conductive material is used during the manufacturing of the positive electrode. In addition, as the amount of binder used during the manufacturing of the positive electrode decreases, the amount of positive electrode active material can be increased, so that the rechargeable lithium battery including the positive electrode active material can exhibit high capacity and high energy density characteristics.
[0069] The following describes in detail the configuration of a method for preparing a positive electrode active material according to some example embodiments.
[0070] (i) Steps for preparing core particles
[0071] Prepare core particles comprising lithium cobalt-based composite oxides. The core particles prepared in step (i) can be described in the same way as the core particles in the positive electrode active material described above, and therefore their detailed description is omitted.
[0072] (ii) Preparation of microparticle graphite
[0073] The average size (D) will be in the range of approximately 3 μm to approximately 25 μm. 50 Flake graphite was ground to prepare a material with an average size (D) of less than about 1 μm. 50 The particulate graphite prepared in step (ii) has specific physical properties such as average size, I0, etc. D / I G The values can be described in the same way as those of the particulate graphite in the above-mentioned positive electrode active material, and therefore their detailed description is omitted below.
[0074] The average size (D) of the flake graphite used in step (ii) of preparing particulate graphite 50 The size of the flake graphite can be less than or equal to about 24 μm, less than or equal to about 23 μm, less than or equal to about 22 μm, less than or equal to about 21 μm, or less than or equal to about 20 μm, and can be greater than or equal to about 5 μm, greater than or equal to about 7 μm, or greater than or equal to about 10 μm. In this paper, the average size of the flake graphite can be measured by scanning electron microscopy images. In this paper, the average size of the flake graphite (D...) 50 This can be measured by a particle size analyzer and represents the size of particles that constitute 50% of the total volume in the particle size distribution. Furthermore, the particle size here can refer to the length of the longest axis in a plane perpendicular to the thickness direction within the plate shape.
[0075] Flake graphite may have a Raman spectrum at 1350 cm⁻¹ in the range of about 0.01 to about 0.15, for example about 0.02 to about 0.14, about 0.08 to about 0.14, or about 0.1 to about 0.14. -1 Nearby peak intensity (I) D ) at 1580 cm -1 Nearby peak intensity (I) G The ratio of (I) D / I G ).
[0076] In step (ii) of preparing particulate graphite, the pulverization of flake graphite can be carried out for a duration of greater than or equal to about 50 minutes, and for example, the pulverization of flake graphite can be carried out for a duration of about 50 minutes to about 200 minutes, about 50 minutes to about 180 minutes, about 50 minutes to about 150 minutes, or about 50 minutes to about 120 minutes. If the time used for pulverizing the flake graphite meets the above range (when the time used for pulverizing the flake graphite meets the above range), the average size (D) of the particulate graphite can be increased. 50To improve the coating yield of particulate graphite on the surface of the core particles in step (iii) below, and to form a carbon coating layer including a large amount of graphene on the surface of the core particles even with a substantially small amount of particulate graphite.
[0077] In step (ii) of preparing particulate graphite, a grinding process can be used to pulverize the flake graphite. The grinding process can utilize methods known to those skilled in the art, and for example, equipment such as ball mills, bead mills, jet mills, pin mills, roller mills, mixing mills, colloid mills, or air classifying mills (ACMs) can be used.
[0078] In step (ii) of preparing particulate graphite, flake graphite can be pulverized by ball milling, using zirconia beads having a size in the range of about 1 mm to about 25 mm, and the milling can be carried out at a speed in the range of about 200 rpm to about 5,000 rpm. The size of the zirconia beads can be in the range of about 1.2 mm to about 23 mm, about 1.3 mm to about 21 mm, or about 1.5 mm to about 20 mm. Furthermore, the pulverization of flake graphite can be carried out under conditions in the range of about 250 rpm to about 4,500 rpm, about 300 rpm to about 4,000 rpm, about 400 rpm to about 3,000 rpm, or about 600 rpm to about 2,000 rpm. When the bead size or stirring speed respectively meets the above ranges, the average size (D) of the particulate graphite is determined by... 50 By controlling the material to the desired level, the coating yield of particulate graphite on the surface of the core particles in step (iii) of obtaining the positive electrode active material can be improved, and a carbon coating layer including a large amount of graphene can be formed on the surface of the core particles even with a substantially small amount of particulate graphite.
[0079] (iii) Steps for obtaining positive electrode active material
[0080] Core particles and particulate graphite are dry-mixed to obtain a positive electrode active material. In step (iii) of obtaining the positive electrode active material, crystalline carbon derived from particulate graphite coats the surface of the core particles, and a carbon coating layer of graphene comprising a layered structure ranging from 2 to 50 layers can be formed on the surface of the core particles. Furthermore, since the average size (D) of the particulate graphite is controlled as desired in step (ii) of preparing the particulate graphite described above, 50Therefore, in step (iii) of obtaining the positive electrode active material, particulate graphite can be coated onto the surface of the core particle with a high coating yield, and thus, even using a substantially small amount of particulate graphite, a carbon coating layer including a large amount of graphene can be formed on the surface of the core particle. Therefore, because the powder resistance of the manufactured positive electrode active material is reduced, conductivity is improved. Furthermore, because a thin and uniform or substantially uniform carbon coating layer is formed on the surface of the core particle in step (iii) of obtaining the positive electrode active material, conductivity and adhesion strength to the electrode plate can be ensured even when a small amount of binder is used during the manufacturing of the positive electrode. In addition, as the amount of binder used during the manufacturing of the positive electrode decreases, the amount of positive electrode active material can increase, enabling the rechargeable lithium battery to exhibit high capacity and high energy density characteristics.
[0081] Based on the total weight of 100% by weight of core particles and particulate graphite, particulate graphite can be mixed in amounts ranging from about 0.02% by weight to about 3.0% by weight, for example, from about 0.02% by weight to about 2.8% by weight, from about 0.03% by weight to about 2.5% by weight, from about 0.05% by weight to about 2.0% by weight, from about 0.05% by weight to about 1.0% by weight, from about 0.05% by weight to about 0.5% by weight, or from about 0.05% by weight to about 0.8% by weight. If the amount of particulate graphite mixed meets the above range (when the amount of particulate graphite mixed meets the above range), the high capacity and high energy density characteristics of rechargeable lithium batteries can be improved, while the conductivity of the positive electrode active material can be improved. For example, even if the amount of particulate graphite mixed is substantially small, less than about 1% by weight (when the amount of particulate graphite mixed is substantially small, less than about 1% by weight), it is still desired to coat the surface of the core particles to increase the electronic conductivity of the positive electrode active material and increase the density of the positive electrode.
[0082] Step (iii) to obtain the positive electrode active material can be performed by mixing core particles and particulate graphite and applying a shear force. In this case, while crystalline carbon derived from particulate graphite is arranged in a two-dimensional plane on the surface of the core particles, a coating layer comprising graphene exhibiting a layered structure with a dense crystalline structure can be formed. For example, this process can be performed using equipment for applying shear force, such as equipment with internal blades, but is not limited thereto.
[0083] In step (iii) of obtaining the positive electrode active material, a mixer, such as a dry mixer (e.g., a Nobilta mixer), can be used to mix the core particles and particulate graphite, and the mixing can be completed in about 1,000 s. -1 From approximately 9,000 s -1The core particles and particulate graphite are mixed at shear rates within the range and blade rotation speeds less than or equal to about 20 m / s.
[0084] Core particles and microparticles of graphite can be produced in approximately 1,500 s. -1 From approximately 8,800 s -1 Approximately 2,000 s -1 From approximately 8,800 s -1 Or approximately 2,500 s -1 From approximately 8,500 s -1 Mixing at shear rates within the specified range. If the range of shear rates meets the above requirements (when the range of shear rates meets the above requirements), a coating layer can be effectively formed on the surface of the core particles, while reducing or preventing damage to the core particles.
[0085] The rotational speed of the blades within the device used to apply shear force can be less than or equal to about 18 m / s, less than or equal to about 15 m / s, or less than or equal to about 10 m / s, and greater than or equal to about 3 m / s, greater than or equal to about 4 m / s, or greater than or equal to about 5 m / s. If the rotational speed of the blades meets the above range (when the rotational speed of the blades meets the above range), a coating layer can be effectively formed on the surface of the core particle, while reducing or preventing damage to the core particle.
[0086] Step (iii) of obtaining the positive electrode active material can be performed at a speed in the range of about 500 rpm to about 6,000 rpm, and for example, at a speed of about 600 rpm to about 5,500 rpm, about 700 rpm to about 5,000 rpm, or about 800 rpm to about 4,000 rpm. If the conditions for performing this step meet the above range (when the conditions for performing this step meet the above range), a coating layer can be effectively formed on the surface of the core particle, while reducing or preventing damage to the core particle.
[0087] In step (iii) of obtaining the positive electrode active material, the core particles and particulate graphite can be mixed using a dry method. In this case, manufacturing costs can be reduced, and the adhesion strength to the electrode plate and the conductivity of the positive electrode active material can be further improved because the coating layer is thin and uniformly or substantially uniformly formed. Herein, "dry method" can mean a state where there is no intentional contact with solvents such as process solvents, or a state where solvents are not intentionally included. For example, dry mixing can be performed using methods known to those skilled in the art, and, for example, a dry mixer, homogenizer, or Henschel mixer can be used.
[0088] In step (iii) of obtaining the positive electrode active material, the coating yield of particulate graphite on the core particle can be greater than or equal to about 55%, for example, greater than or equal to about 60%, greater than or equal to about 65%, or greater than or equal to about 70%, and can be less than or equal to about 99%, less than or equal to about 98%, or less than or equal to about 95%. For example, the ratio of the weight of graphene in the positive electrode active material to the weight of particulate graphite input in step (iii) of obtaining the positive electrode active material can be greater than or equal to about 55%, for example, greater than or equal to about 60%, greater than or equal to about 65%, or greater than or equal to about 70%, and can be less than or equal to about 99%, less than or equal to about 98%, or less than or equal to about 95%. Here, the coating yield of particulate graphite on the core particle can be the coating yield calculated using a carbon / sulfur (CS) analyzer, and can be calculated, for example, by the method described in Evaluation Example 2 below. That is, because the average size (D) of the particulate graphite is controlled as desired in step (ii) of preparing particulate graphite as described above. 50 Therefore, in step (iii) of obtaining the positive electrode active material, particulate graphite can be coated on the surface of the core particles with a high coating yield, and thus, even with a substantially small amount of particulate graphite, a carbon coating layer including a large amount of graphene can be formed on the surface of the core particles.
[0089] positive electrode
[0090] In some example embodiments, the positive electrode includes a positive electrode current collector and a layer of positive electrode active material on the positive electrode current collector, wherein the positive electrode active material layer includes the aforementioned positive electrode active material. In addition to the aforementioned positive electrode active material, the positive electrode active material layer may further include other types of positive electrode active materials. For example, based on the total weight of 100% of the positive electrode active material layer, the positive electrode active material may be included in amounts ranging from about 60% to about 99.9% by weight, about 70% to about 99.9% by weight, about 80% to about 99.9% by weight, about 90% to about 99.9% by weight, or about 95% to about 99.9% by weight.
[0091] The configuration of the positive electrode according to some example embodiments is described in detail below.
[0092] current collector
[0093] There are no particular limitations on the current collector, as long as it is conductive and does not cause adverse chemical changes in the positive electrode and in the rechargeable lithium battery including the positive electrode. For example, the current collector may include a thin film of at least one of the following: aluminum (Al), stainless steel (SUS), indium (In), magnesium (Mg), titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), germanium (Ge), lithium (Li), or combinations thereof, and may include, for example, an aluminum thin film.
[0094] Current collectors can take many forms, such as plates, thin sheets, films, sheets, foils, meshes, porous bodies, foams, or nonwoven materials. For example, current collectors can include microscopic irregularities on their surface, which can improve the adhesion strength to the positive electrode active material.
[0095] The thickness of the current collector can be in the range of about 1 μm to about 20 μm, for example about 5 μm to about 15 μm or about 7 μm to about 10 μm.
[0096] adhesive
[0097] The binder improves the adhesion properties between the positive electrode active material particles and with the current collector. For example, the binder may include one or more of, but is not limited to, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers (polymers containing ethylene oxide), polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, epoxy resin, (meth)acrylate resin, polyester resin, and nylon.
[0098] Based on the total weight of 100% by weight of the positive electrode active material layer, the binder may be included in an amount ranging from about 0.1% by weight to about 1% by weight, and for example, less than about 1.0% by weight or less than or equal to about 0.9% by weight.
[0099] conductive materials
[0100] The conductive material is included to provide electrode conductivity, and any electrically conductive material can be used as the conductive material unless it causes an adverse chemical change in the battery. For example, the conductive material may include at least one of carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, carbon nanofiber, carbon nanotube, etc.; metal-based materials including at least one of metal powders or metal fibers such as copper, nickel, aluminum, silver, etc.; conductive polymers such as polyphenylene derivatives; or mixtures thereof.
[0101] Based on the total weight of 100% by weight of the positive electrode active material layer, the conductive material may be included in amounts ranging from about 0% to about 1% by weight, for example from about 0.05% to about 1% by weight, less than about 1.0% by weight, less than or equal to about 0.8% by weight, less than or equal to about 0.7% by weight, or less than or equal to about 0.5% by weight. Because the positive electrode active material layer includes the aforementioned positive electrode active material, even if the positive electrode active material layer does not include a separate conductive material or includes a substantially small amount of conductive material (even when the positive electrode active material layer does not include a separate conductive material or includes a substantially small amount of conductive material), it can exhibit the desired or improved electronic conductivity and achieve low resistance and high positive electrode density.
[0102] As an example, the density of the positive electrode active material layer can be in the range of about 2.0 g / cc to about 6.0 g / cc, for example, about 2.3 g / cc to about 5.8 g / cc, about 2.5 g / cc to about 5.7 g / cc, or about 2.5 g / cc to about 5.5 g / cc. Alternatively, for example, when the lithium transition metal composite oxide of the core particle is a lithium cobalt-based oxide, the density of the positive electrode active material layer can be in the range of about 3.5 g / cc to about 5.0 g / cc, about 3.7 g / cc to about 4.9 g / cc, about 3.8 g / cc to about 4.8 g / cc, or about 4.0 g / cc to about 4.5 g / cc. If the density of the positive electrode active material layer meets the above range (when the density of the positive electrode active material layer meets the above range), the energy density of the rechargeable lithium battery can be improved. For example, because the above-mentioned positive electrode active material has high particle strength and particle surface lubricity, compression processes can be performed at higher pressures. Furthermore, because the surface of the positive electrode active material has high lubricity, the compression efficiency of the positive electrode can be increased through a sliding effect. For example, because the compression process can be carried out at higher pressures, the pores in the electrode plates of the positive electrode active material layer can be reduced, and the density of the positive electrode active material layer can be further improved.
[0103] The adhesion strength of the positive electrode active material layer to the current collector can be greater than or equal to about 0.5 gf / mm, and the resistance of the positive electrode active material layer can be less than or equal to about 40 Ω·cm. For example, the adhesion strength of the positive electrode active material layer to the current collector can be greater than or equal to about 1.0 gf / mm, greater than or equal to about 1.5 gf / mm, greater than or equal to about 2.0 gf / mm, or greater than or equal to about 2.5 gf / mm, and can be less than or equal to about 30 gf / mm, less than or equal to about 28 gf / mm, less than or equal to about 25 gf / mm, or less than or equal to about 23 gf / mm. Additionally, for example, the resistance of the positive electrode active material layer may be less than or equal to about 35 Ω·cm, less than or equal to about 30 Ω·cm, less than or equal to about 25 Ω·cm, or less than or equal to about 20 Ω·cm, and may be greater than or equal to about 0.5 Ω·cm, greater than or equal to about 1.0 Ω·cm, greater than or equal to about 3.0 Ω·cm, greater than or equal to about 5.0 Ω·cm, or greater than or equal to about 5.5 Ω·cm. For example, because the positive electrode active material layer includes the aforementioned positive electrode active material, even if the positive electrode active material layer does not include a separate conductive material or includes a substantially small amount of conductive material (even when the positive electrode active material layer does not include a separate conductive material or includes a substantially small amount of conductive material), the positive electrode active material layer can exhibit the desired or improved electronic conductivity and achieve low resistance, and even if the positive electrode active material layer includes a substantially small amount of binder (even when the positive electrode active material layer includes a substantially small amount of binder), the positive electrode active material layer can achieve high adhesion strength to the electrode plate.
[0104] The porosity of the positive electrode can be less than or equal to about 30%, less than or equal to about 25%, or less than or equal to about 20% and greater than or equal to about 1%, greater than or equal to about 5%, or greater than or equal to about 7%. If the porosity of the positive electrode meets the above ranges (when the porosity of the positive electrode meets the above ranges), the capacity and energy density of the positive electrode can be improved. In this paper, the porosity of the positive electrode means the ratio of the volume of pores present within the positive electrode to the total volume of the positive electrode, and can be measured, for example, by mercury porosimetry (mercury porosimetry).
[0105] Rechargeable lithium batteries
[0106] A rechargeable lithium battery according to some example embodiments includes a positive electrode, a negative electrode, and an electrolyte. The positive electrode includes a current collector and a layer of positive electrode active material on the current collector, wherein the layer of positive electrode active material includes the aforementioned positive electrode active material. The rechargeable lithium battery may be or include a lithium-ion battery using a liquid electrolyte, or an all-solid-state rechargeable battery or a semi-solid-state rechargeable battery using a solid electrolyte. For convenience, the configuration of the lithium-ion battery is described in detail below.
[0107] Depending on their shape, rechargeable lithium batteries can be classified as cylindrical, prismatic, pouch-shaped, coin-shaped, etc. Figures 1 to 4 To illustrate a schematic diagram of a rechargeable lithium battery according to some example embodiments, wherein Figure 1 It is a cylindrical battery. Figure 2 It is a prismatic battery, and Figure 3 and Figure 4 It is a pouch-shaped battery.
[0108] Reference Figures 1 to 4 The rechargeable lithium battery 100 includes an electrode assembly 40 and a housing 50. The electrode assembly 40 has a separator 30 inserted between a positive electrode 10 and a negative electrode 20. The electrode assembly 40 is housed within the housing 50. The positive electrode 10, the negative electrode 20, and the separator 30 may be impregnated with an electrolyte solution (not shown). The rechargeable lithium battery 100 may include a sealing member 60 that seals the housing 50, such as... Figure 1 As shown. In Figure 2 In this rechargeable lithium battery 100, a positive electrode lead connector 11, a positive electrode terminal 12 connected to the positive electrode lead connector 11, a negative electrode lead connector 21, and a negative electrode terminal 22 connected to the negative electrode lead connector 21 are included. Figure 3 and Figure 4 As shown, the rechargeable lithium battery 100 includes Figure 4 The electrode terminals 70 shown in the figure or Figure 3 The positive electrode terminal 71 and negative electrode terminal 72 shown in the figure form an electrical path for leading the current generated in the electrode assembly 40 to the outside of the battery 100.
[0109] Rechargeable lithium batteries according to some example embodiments may be rechargeable at high voltages or suitable for driving at high voltages. For example, the charging voltage of a rechargeable lithium battery may be greater than or equal to about 4.45 V, about 4.45 V to about 4.7 V, about 4.45 V to about 4.6 V, or about 4.45 V to about 4.55 V. By applying the positive electrode active material according to some example embodiments, rechargeable lithium batteries can significantly reduce the amount of gas generated even when charged at high voltages, and can achieve high capacity and long cycle life characteristics.
[0110] negative electrode
[0111] The negative electrode may include a current collector and a layer of negative electrode active material on the current collector. The negative electrode active material layer includes a negative electrode active material and may further include a binder, a conductive material, or a combination thereof.
[0112] Negative electrode active material
[0113] The negative electrode active material may include at least one of the following: a material capable of reversibly intercalating / deintercalating lithium ions, lithium metal, a lithium metal alloy, a material capable of doping / dedoping lithium, or a transition metal oxide.
[0114] The material capable of reversibly intercalating / deintercalating lithium ions may include, for example, crystalline carbon, amorphous carbon, or a combination thereof as a carbon-based negative electrode active material. The crystalline carbon may be irregular, or flake-like, scaly, spherical, or fibrous natural graphite or artificial graphite. The amorphous carbon may be or include at least one of soft carbon, hard carbon, mesophase pitch carbonized products, calcined coke, and the like.
[0115] The lithium metal alloy includes an alloy of lithium and a metal, and the metal is, for example, or includes at least one of the following: Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, and Sn.
[0116] The material capable of doping / dedoping lithium may be or include a Si-based negative electrode active material or a Sn-based negative electrode active material. The Si-based negative electrode active material may include at least one of the following: silicon, a silicon-carbon composite, SiO x (0<x≤2), a Si-Q alloy (where Q is, for example, or includes at least one of the following elements: an alkali metal, an alkaline earth metal, a Group 13 element, a Group 14 element (other than Si), a Group 15 element, a Group 16 element, a transition metal, a rare earth element, and combinations thereof, for example, at least one of Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Tl, Ge, P, As, Sb, Bi, S, Se, Te, Po, and combinations thereof), or a combination thereof. The Sn-based negative electrode active material may be or include at least one of the following: Sn, SnO2, a Sn alloy, or a combination thereof.
[0117] The silicon-carbon composite may be or include a composite of silicon and amorphous carbon. The average particle diameter (D 50 ) of the silicon-carbon composite particles may, for example, be in the range of about 0.5 μm to about 20 μm. According to some example embodiments, the silicon-carbon composite may be in the form of silicon particles and amorphous carbon coated on the surfaces of the silicon particles. For example, the silicon-carbon composite may include secondary particles (core) in which silicon primary particles are aggregated, and an amorphous carbon coating layer (shell) on the surfaces of the secondary particles. Amorphous carbon may also be present between the silicon primary particles, for example, the silicon primary particles may be coated with amorphous carbon. The secondary particles may be dispersed in an amorphous carbon matrix.
[0118] The silicon-carbon composite may further include crystalline carbon. For example, the silicon-carbon composite may include a core comprising crystalline carbon and silicon particles, and an amorphous carbon coating layer on the surface of the core. The crystalline carbon may be or include artificial graphite, natural graphite, or a combination thereof. The amorphous carbon may include at least one of soft carbon or hard carbon, a mesophase pitch carbonized product, and calcined coke.
[0119] When the silicon-carbon composite includes silicon and amorphous carbon, based on 100 wt% of the silicon-carbon composite, the amount of silicon may be in the range of about 10 wt% to about 50 wt%, and the amount of amorphous carbon may be in the range of about 50 wt% to about 90 wt%. In addition, when the silicon-carbon composite includes silicon, amorphous carbon, and crystalline carbon, based on 100 wt% of the silicon-carbon composite, the amount of silicon may be in the range of about 10 wt% to about 50 wt%, the amount of crystalline carbon may be in the range of about 10 wt% to about 70 wt%, and the amount of amorphous carbon may be in the range of about 20 wt% to about 40 wt%.
[0120] For example, the thickness of the amorphous carbon coating layer may be in the range of about 5 nm to about 100 nm. The average particle diameter (D 50 ) of the silicon particles (primary particles) may be in the range of about 10 nm to about 1 μm or about 10 nm to about 200 nm. The silicon particles may be in the form of elemental silicon, a silicon alloy, or an oxidized form. The oxidized form of silicon may be represented by SiO x (0<x≤2). For example, the atomic content ratio of Si:O indicating the oxidation degree may be in the range of about 99:1 to about 33:67.
[0121] The Si-based negative electrode active material or Sn-based negative electrode active material may be mixed with the carbon-based negative electrode active material. When the Si-based negative electrode active material or Sn-based negative electrode active material is used in combination with the carbon-based negative electrode active material, the weight ratio of the Si-based negative electrode active material or Sn-based negative electrode active material to the carbon-based negative electrode active material may be in the range of about 1:99 to about 90:10.
[0122] The negative electrode active material may be included in an amount in the range of about 80 wt% to about 99 wt%, for example, about 85 wt% to about 99 wt% or about 90 wt% to about 99 wt%, based on 100 wt% of the total weight of the negative electrode active material layer.
[0123] adhesive
[0124] The binder adheres the negative electrode active material particles to each other and adheres the negative electrode active material to the current collector. The binder may be or include a non-aqueous binder, an aqueous binder, a dry binder, or a combination thereof.
[0125] Non-aqueous adhesives may include at least one of the following: polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene-propylene copolymer, polystyrene, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamide-imide, polyimide, or combinations thereof.
[0126] Waterborne adhesives may include at least one of the following: styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, (meth)acrylonitrile-butadiene rubber, (meth)acrylic rubber, butyl rubber, fluororubber, polyethylene oxide, polyvinylpyrrolidone, polyepoxygenated alcohol, polyphosphazene, poly(meth)acrylonitrile, ethylene propylene diene copolymer, polyvinylpyridine, chlorosulfonated polyethylene, latex, polyester resin, (meth)acrylic resin, phenolic resin, epoxy resin, polyvinyl alcohol, or combinations thereof.
[0127] When an aqueous binder is used as the negative electrode binder, it may further include a cellulose-based compound capable of imparting viscosity. As a cellulose-based compound, one or more of carboxymethyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose, or their alkali metal salts may be mixed and used. The alkali metal may be or include at least one of Na, K, or Li.
[0128] Dry adhesives may be or include polymeric materials capable of being converted into fibers, and may be or include at least one of the following: polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyethylene oxide, or combinations thereof.
[0129] Based on the total weight of 100% by weight of the negative electrode active material layer, the binder may be included in an amount ranging from about 0.5% by weight to about 5% by weight, for example from about 0.5% by weight to about 4% by weight, or from about 1% by weight to about 3% by weight.
[0130] conductive materials
[0131] The conductive material is included to provide electrode conductivity, and any electrically conductive material can be used as the conductive material unless it causes an adverse chemical change in the battery. Examples of conductive materials include at least one carbon-based material such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, carbon nanofiber, carbon nanotube, etc.; metal-based materials including at least one metal powder or metal fiber of copper, nickel, aluminum, silver, etc.; conductive polymers such as polyphenylene derivatives; or mixtures thereof.
[0132] Based on the total weight of 100% by weight of the negative electrode active material layer, the conductive material may be included in an amount ranging from about 0.5% by weight to about 5% by weight, for example from about 0.5% by weight to about 4% by weight, or from about 1% by weight to about 3% by weight.
[0133] current collector
[0134] There are no particular restrictions on the negative electrode current collector, as long as it does not cause adverse chemical changes in the negative electrode and the rechargeable lithium battery including the negative electrode. For example, the negative electrode current collector may be or include at least one of the following: copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, polymer substrate coated with a conductive metal, or a combination thereof.
[0135] Negative electrode current collectors can take many forms, such as plates, thin sheets, films, sheets, foils, meshes, porous bodies, foams, or nonwoven materials. For example, negative electrode current collectors can include microscopic irregularities on their surface, which can improve the adhesion strength to the negative electrode active material.
[0136] The thickness of the negative electrode current collector can be in the range of about 1 μm to about 20 μm, for example about 5 μm to about 15 μm or about 7 μm to about 10 μm.
[0137] electrolytes
[0138] For example, the electrolyte used in a rechargeable lithium battery may be or include an electrolyte solution and may include a non-aqueous organic solvent and a lithium salt.
[0139] Non-aqueous organic solvents constitute the medium for transporting ions that participate in the electrochemical reactions of the battery. Non-aqueous organic solvents may be or include at least one of the following: carbonate-based solvents, ester-based solvents, ether-based solvents, ketone-based solvents, alcohol-based solvents, aprotic solvents, or combinations thereof.
[0140] Carbonate solvents may include at least one of the following: dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), butyl carbonate (BC), etc.
[0141] Ester solvents may include at least one of the following: methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, decanoic acid lactone, mevalonate lactone, caprolactone, etc.
[0142] Ether solvents may include at least one of the following: dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, dimethoxyethane, 2-methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, tetrahydrofuran, etc.
[0143] Ketone solvents may include cyclohexanone, etc. Alcohol solvents may include ethanol, isopropanol, etc. Aprotic solvents may include at least one of the following: nitriles such as R-CN (where R is a C2 to C20 straight-chain, branched or cyclic hydrocarbon group, and may include double bonds, aromatic rings or ether groups, etc.); amides such as dimethylformamide; dioxolane such as 1,3-dioxolane, 1,4-dioxolane, etc.; sulfolane, etc.
[0144] Non-aqueous organic solvents can be used alone or in mixtures of two or more types of solvents, and when two or more types of solvents are used in mixtures, the mixing ratio can be adjusted as desired to achieve the desired battery performance, as is widely known to those skilled in the art.
[0145] When using carbonate solvents, cyclic carbonates and chain carbonates can be mixed together, and the cyclic carbonates and chain carbonates can be mixed in a volume ratio ranging from about 1:1 to about 1:9.
[0146] Non-aqueous organic solvents may further include aromatic hydrocarbon organic solvents. For example, carbonate solvents and aromatic hydrocarbon organic solvents may be mixed together in a volume ratio ranging from about 1:1 to about 30:1.
[0147] The electrolyte solution may further include at least one of vinylene carbonate, vinylene carbonate, or ethylene carbonate compounds to improve battery cycle life.
[0148] Examples of ethylene carbonate compounds may include at least one of the following: fluoroethylene carbonate, difluoroethylene carbonate, chloroethylene carbonate, dichloroethylene carbonate, bromoethylene carbonate, dibromoethylene carbonate, nitroethylene carbonate, and cyanoethylene carbonate.
[0149] Lithium salts dissolved in organic solvents supply lithium ions in the battery, enabling basic operation of rechargeable lithium batteries and improving lithium ion transport between the positive and negative electrodes. Examples of lithium salts may include at least one of the following: LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiAlO2, LiAlCl4, LiPO2F2, LiCl, LiI, LiN(SO2C2F5)2, Li(FSO2)2N (lithium bis(fluorosulfonyl)imide; LiFSI), LiC4F9SO3, LiN(C x F 2x+1 SO2)(C y F 2y+1 SO2 (where x and y are integers in the range of 1 to 20), lithium trifluoromethanesulfonate, lithium tetrafluoroethanesulfonate, lithium difluorobis(oxalate)phosphate (LiDFBOP), and lithium bis(oxalate)borate (LiBOB).
[0150] The concentration of lithium salt can be in the range of about 0.1 M to about 2.0 M. If the concentration of lithium salt is in the above range (when the concentration of lithium salt is in the above range), the electrolyte solution has the desired ionic conductivity and viscosity, and therefore the desired or improved performance can be achieved and lithium ions can move efficiently.
[0151] diaphragm
[0152] Depending on the type of rechargeable lithium battery, the rechargeable lithium battery may further include a separator between the positive and negative electrodes. The separator may include at least one of the following: polyethylene, polypropylene, polyvinylidene fluoride, or a multilayer membrane of two or more layers thereof, and mixed multilayer membranes such as a polyethylene / polypropylene two-layer separator, a polyethylene / polypropylene / polyethylene three-layer separator, a polypropylene / polypropylene / polypropylene three-layer separator, etc.
[0153] The diaphragm may include a porous substrate and a coating on one or both surfaces of the porous substrate, comprising organic materials, inorganic materials, or combinations thereof.
[0154] The porous substrate may be or include a polymer membrane, which is formed from or includes any one or more of the following: polyolefins such as polyethylene and polypropylene, polyesters such as polyethylene terephthalate and polybutylene terephthalate, polyacetal, polyamide, polyimide, polycarbonate, polyetherketone, polyaryletherketone, polyetherimide, polyamideimide, polybenzimidazole, polyethersulfone, polyphenylene ether, cyclic olefin copolymers, polyphenylene sulfide, polyethylene naphthalate, Teflon (polytetrafluoroethylene), or copolymers or mixtures of two or more thereof. The porous substrate may include glass fiber, or may include a composite membrane of polymer and glass fiber.
[0155] The porous substrate may have a thickness in the range of about 1 μm to about 40 μm, for example about 1 μm to about 30 μm, about 1 μm to about 20 μm, about 5 μm to about 15 μm, or about 10 μm to about 15 μm.
[0156] Organic materials may include (meth)acrylic acid copolymers, which include a first structural unit and a second structural unit derived from (meth)acrylamide, wherein the second structural unit includes at least one structural unit derived from (meth)acrylic acid or (meth)acrylate and a structural unit derived from (meth)acryloylsulfamic acid or a salt thereof.
[0157] Inorganic materials may include inorganic particles, which may include, for example, at least one of the following: Al₂O₃, SiO₂, TiO₂, SnO₂, CeO₂, MgO, NiO, CaO, Ga₂O₃, ZnO, ZrO₂, Y₂O₃, SrTiO₃, BaTiO₃, Mg(OH)₂, boehmite, and combinations thereof, but are not limited thereto. The average particle size (D) of the inorganic particles... 50 The range can be from about 1 nm to about 2000 nm, for example from about 100 nm to about 1000 nm, or from about 100 nm to about 700 nm. In this paper, the average particle size (D) of the inorganic particles is... 50 The particle size distribution can be obtained by randomly selecting about 20 particles from a scanning electron microscope image of inorganic particles, measuring their particle size (diameter, major axis, or major axis length) to obtain the particle size distribution, and then taking the size of the particles with a cumulative volume of 50% of the particle size distribution as the average particle size.
[0158] Organic and inorganic materials can be mixed in a single coating, or a coating comprising organic materials and a coating comprising inorganic materials can be stacked together. The thickness of the coating can range from about 0.5 μm to about 20 μm, for example from about 1 μm to about 10 μm, or from about 1 μm to about 5 μm.
[0159] The rechargeable lithium battery according to some example embodiments may be applicable to, for example, automobiles, mobile phones or various types of electronic devices, but is not limited thereto.
[0160] The following describes embodiments and comparative examples of this disclosure. However, the following embodiments are merely examples of this disclosure, and this disclosure is not limited to the following embodiments.
[0161] Example 1
[0162] (1) Preparation of positive electrode active material
[0163] Core particle preparation: Prepare particles with an average diameter (D) of 14.94 μm. 50 LiCoO2 (LCO) was used as the core particle.
[0164] Preparation of particulate graphite: Flake graphite (G5 (C-one)) with an average particle size (D) was prepared. 50 (17.94 μm) and ZrO2 beads with a particle size of 2 mm, corresponding to 10 times the weight of the flake graphite, were mixed. The flake graphite was then milled at 1,000 rpm for 1 hour to prepare particulate graphite. At this point, the average size (D) of the particulate graphite was measured using a particle size analyzer with laser diffraction. 50 The value is 0.33 μm.
[0165] Obtaining the positive electrode active material: 99.8 wt% core particles and 0.2 wt% particulate graphite were fed into a dry mixer. The shear rate was adjusted to 7,000 s⁻¹. -1 After adjusting the rotation speed of the blades in the mixer to 4.7 m / s, the core particles and microparticle graphite were mixed for 10 minutes to obtain the positive electrode active material.
[0166] (2) Manufacturing of the positive electrode
[0167] A positive electrode active material slurry was prepared by dispersing 99.1 wt% of the positive electrode active material prepared in (1), 0.2 wt% of carbon nanotubes as a conductive material, and 0.7 wt% of polyvinylidene fluoride as a binder in N-methylpyrrolidone (NMP) solvent. The positive electrode active material slurry was coated onto a 12 μm thick aluminum substrate (current collector) and dried to form a positive electrode active material layer, which was then compressed to manufacture a positive electrode. In the manufactured positive electrode, the loading level of the positive electrode active material layer was 16 mg / cm². 2 The density of the positive electrode active material layer was 3.38 g / cc. Furthermore, SEM analysis of the compressed positive electrode confirmed that the thickness of the positive electrode active material layer was approximately 50 μm.
[0168] (3) Manufacturing of rechargeable lithium battery cells
[0169] The positive electrode and lithium metal counter electrode manufactured in (2) are used, with a separator having a polyethylene-polypropylene multilayer structure inserted between them. The rechargeable lithium battery cell is manufactured by conventional methods by injecting an electrolyte solution prepared by adding 1.3 M LiPF6 lithium salt to a solvent comprising ethylene carbonate, propylene carbonate and propyl propionate mixed in a volume ratio of 10:15:75.
[0170] Example 2
[0171] The positive electrode active material, positive electrode, and rechargeable lithium battery cell were manufactured using essentially the same method as in Example 1, except that: in the process of “(1) Preparation of the positive electrode active material” in Example 1, the grinding time for the flake graphite was changed to 50 minutes (the average size of the particulate graphite (D)). 50 (0.48 μm)
[0172] Comparative Example 1
[0173] (1) Preparation of positive electrode active material
[0174] Core particle preparation: Prepare particles with an average diameter (D) of 14.94 μm.50 LiCoO2 (LCO) was used as the core particle.
[0175] Obtaining the positive electrode active material: 99.8% by weight of core particles and 0.2% by weight of flake graphite (G5 (C-one)), with an average particle size (D... 50 (17.94 μm) was added to the dry mixer. The shear rate was adjusted to 7000 s⁻¹. -1 After adjusting the rotation speed of the blades in the mixer to 4.7 m / s, the core particles and flake graphite were mixed for 10 minutes to obtain the positive electrode active material.
[0176] (2) Manufacturing of positive electrode and rechargeable lithium battery cell
[0177] Using the positive electrode active material of Comparative Example 1 prepared in (1) above, the positive electrode active material, the positive electrode and the rechargeable lithium battery cell were manufactured by a method substantially the same as that in Example 1.
[0178] Comparative Example 2
[0179] The positive electrode active material, positive electrode, and rechargeable lithium battery cell were manufactured using essentially the same method as in Example 1, except that: in the process of “(1) Preparation of the positive electrode active material” in Example 1, the grinding time for the flake graphite was changed to 30 minutes (the average size of the particulate graphite (D)). 50 (2.4 μm).
[0180] Scanning electron microscope (SEM) images of the surface of graphite used on the core particles of Example 1, Comparative Example 1, and Comparative Example 2 are shown sequentially. Figures 5 to 7 middle. Figure 5 This is a scanning electron microscope image of the surface of the particulate graphite used during the preparation of the positive electrode active material in Example 1. Figure 6 These are scanning electron microscope images of the surface of the sheet graphite used during the preparation of the positive electrode active material in Comparative Example 1; and Figure 7 This is a scanning electron microscope image of the surface of particulate graphite used during the preparation of the positive electrode active material in Comparative Example 2.
[0181] Reference Figures 5 to 7 As the time for pulverizing flake graphite increases, the average size (D) of microparticle graphite decreases. 50 () decrease.
[0182] Comparative Example 3
[0183] The positive electrode active material, positive electrode, and rechargeable lithium battery cell were manufactured using essentially the same method as in Example 1, except that: in the process of “(1) Preparation of the positive electrode active material” in Example 1, the grinding time for the flake graphite was changed to 40 minutes (the average size of the particulate graphite (D)). 50 (1.57 μm).
[0184] Evaluation Example 1: Electron Microscope Image Analysis
[0185] Scanning electron microscope images of the surfaces of the positive electrode active materials prepared in Example 1, Comparative Example 1, and Comparative Example 2 are shown sequentially. Figures 8 to 10 A transmission electron microscope image of the cross-section of the positive electrode active material prepared in Example 1 is shown in the figure. Figure 11 middle. Figure 8 These are scanning electron microscope images of the surface of the positive electrode active material prepared in Example 1. Figure 9 These are scanning electron microscope images of the surface of the positive electrode active material prepared in Comparative Example 1, and Figure 10 This is a scanning electron microscope image of the surface of the positive electrode active material prepared in Comparative Example 2.
[0186] refer to Figures 8 to 10 In the positive electrode active material of Example 1, unlike Comparative Examples 1 and 2, the carbon coating layer is uniformly formed on the surface of the core particles and is in the form of a film continuously surrounding the surface of the core particles. That is, when the average size (D) of the particulate graphite is controlled... 50 When the coating yield of microparticle graphite on the surface of the core particles is improved, a carbon coating layer including a large amount of graphene is formed on the surface of the core particles.
[0187] In addition, the cross-section of the positive electrode active material of Example 1 was observed by transmission electron microscopy (TEM). (Refer to...) Figure 11 The results confirmed that the carbon coating layer comprises graphene with a layered structure of about 20 layers, and the thickness of the carbon coating layer is about 6.251 nm to about 8.296 nm.
[0188] Evaluation Example 2: Measurement of the physical properties of the active material of the positive electrode
[0189] For the positive electrode active materials prepared in the examples and comparative examples, the coating yield and powder resistance were analyzed, and the results are shown in Table 1 below.
[0190] The specific evaluation methods are as follows.
[0191] (1) Coating yield
[0192] The coating yield on the surface of the core particle was measured using a CS analyzer. Specifically, the amount of carbon (C1) in the positive electrode active material (i.e., the core particle itself) without a carbon coating layer was measured using a CS analyzer. Additionally, the amount of carbon (C2) in each positive electrode active material of the examples and comparative examples was measured using a CS analyzer. The amount of carbon (C2) in the positive electrode active material is then shown in Table 1 below as the amount of graphene on the surface of the core particle.
[0193] Independently, for each positive electrode active material of the examples and comparative examples, after removing residual graphite not used for coating using an airflow classifier (rotor speed: 40 Hz; based on approximately 50 g of positive electrode active material, 5 minutes), the amount of carbon (C3) of the obtained product was measured using a CS analyzer.
[0194] Based on the measured amount of carbon, the coating yield is calculated using the following equation:
[0195] Equation:
[0196] Coating yield = 100 × (C3–C1) / (C2–C1).
[0197] (2) Powder resistor
[0198] Using a powder resistance meter (MCP-PD600, Nittoseiko Analytech Co.), 1 g of positive electrode active material was pressurized from 0 to 20 kN, and the powder resistance at 20 kN was measured.
[0199] Evaluation Example 3: Performance Analysis of a Rechargeable Lithium-ion Battery Cell
[0200] The energy density of the rechargeable lithium battery cells manufactured in the Examples and Comparative Examples was analyzed, and the results are shown in Table 1 below.
[0201] The specific evaluation methods are as follows.
[0202] After the compressed electrode plate is stamped to a diameter of 14 mm, the thickness is measured to calculate the density of the mixture layer (positive electrode active material layer). The energy density is then calculated by multiplying the density of the mixture layer (positive electrode active material layer), the fraction of active material, and the initial discharge capacity.
[0203] Table 1:
[0204]
[0205] Referring to Table 1, in Examples 1 and 2, the amount of graphene (C2, based on 100% by weight of positive electrode active material) was 0.097% by weight to 0.103% by weight, the coating yield was 69.4% to 73.3%, the powder resistivity was 3,483 Ω·cm to 7,950 Ω·cm, and the energy density was 778 mAh / cc to 782 mAh / cc.
[0206] Conversely, compared to Examples 1 and 2, in Comparative Example 1, the amount of graphene was measured to be substantially low, the coating yield was measured to be substantially low, the powder resistance was measured to be substantially high, and the energy density was measured to be substantially low. That is, by including the carbon coating layer, the powder resistance of the positive electrode active material is reduced, thereby improving the electrical conductivity of the positive electrode active material.
[0207] In addition, compared with Examples 1 and 2, the average size (D) of the particulate graphite therein is higher. 50 In the cases of Comparative Examples 2 and 3, which are substantially high, the amount of graphene is low, the coating yield is low, the powder resistance is high, and the energy density is low. That is, by controlling the size of the graphene in the carbon coating layer, the coating yield of particulate graphite on the surface of the core particles is improved, and the powder resistance of the positive electrode active material is further reduced.
[0208] While this disclosure has been described with respect to exemplary embodiments that are now considered practical, it will be understood that this disclosure is not limited to the disclosed embodiments. Rather, this disclosure is intended to cover various modifications and equivalent arrangements that are included within the spirit and scope of the appended claims.
[0209] Description of reference numerals in the attached figures:
[0210] 100: Rechargeable lithium battery; 10: Positive electrode
[0211] 11: Positive electrode lead connector 12: Positive electrode terminal
[0212] 20: Negative electrode 21: Negative electrode lead connector
[0213] 22: Negative electrode terminal; 30: Diaphragm
[0214] 40: Electrode assembly; 50: Housing
[0215] 60: Sealing component; 70: Electrode terminal piece
[0216] 71: Positive electrode connector; 72: Negative electrode connector
Claims
1. Positive electrode active material, including: Including core particles of lithium cobalt-based composite oxides; and A carbon coating layer on the surface of the core particles; The carbon coating layer comprises graphene having a layered structure ranging from 2 to 50 layers, and The size of the graphene, as measured by electron microscopy images of the surface of the positive electrode active material, is less than 1 μm.
2. The positive electrode active material according to claim 1, wherein the graphene has a size in the range of 0.01 μm to 0.6 μm.
3. The positive electrode active material according to claim 1, wherein the thickness of the graphene is less than or equal to 20 nm.
4. The positive electrode active material according to claim 1, wherein the graphene has a Raman spectrum at 1350 cm⁻¹ in the range of 0.15 to 0.
50. -1 Nearby peak intensity I D At 1580 cm -1 Nearby peak intensity I G The ratio I D / I G .
5. The positive electrode active material according to claim 1, wherein the graphene of the carbon coating layer is included in an amount ranging from 0.09% to 3.0% by weight based on 100% by weight of the total weight of the positive electrode active material.
6. The positive electrode active material according to claim 1, wherein the graphene in the carbon coating layer is derived from having an average size D of less than 1 μm as measured by a particle size analyzer using laser diffraction. 50 Microparticle graphite.
7. The positive electrode active material according to claim 1, wherein the carbon coating layer is in the form of a film continuously surrounding the surface of the core particle.
8. The positive electrode active material according to claim 1, wherein the core particles comprise a lithium-cobalt-based composite oxide represented by chemical formula 1: Chemical Formula 1: Li a1 Co x1 M 1 y1 O 2-b1 X b1 ; in: 0.9≤a1≤1.8, 0.7≤x1≤1, 0≤y1≤0.3, 0.9≤x1+y1≤1.1, and 0≤b1≤0.1; M 1 Including one or more of Al, B, Ba, Ca, Ce, Cr, Cu, Fe, Mg, Mn, Mo, Ni, Se, Si, Sn, Sr, Ti, V, W, Y, Zn, and Zr; and X includes one or more of F, P, and S.
9. The positive electrode active material according to claim 1, wherein the size of the graphene is relative to the average particle size D of the core particles. 50 The ratio is less than 0.
1.
10. The positive electrode active material according to claim 1, wherein the core particles comprise: Having an average particle size D in the range of 8 μm to 20 μm 50 The first particle; and It has an average particle size D in the range of 0.5 μm to 6 μm. 50 The second particle.
11. The positive electrode active material according to claim 1, wherein the powder resistivity of the positive electrode active material is less than or equal to 10,000 Ω·cm.
12. Positive electrode active material, including: Including core particles of lithium cobalt-based composite oxides; and A carbon coating layer on the surface of the core particles; The carbon coating layer comprises graphene having a layered structure ranging from 2 to 50 layers, and The graphene comprising the carbon coating layer is included in an amount greater than or equal to 0.09% by weight, based on the total weight of 100% by weight of the positive electrode active material.
13. The positive electrode active material according to claim 12, wherein the graphene of the carbon coating layer is included in an amount ranging from 0.09% to 3.0% by weight based on 100% by weight of the total weight of the positive electrode active material.
14. The positive electrode active material according to claim 12, wherein the graphene has a size of less than 1 μm and a thickness of less than or equal to 20 nm.
15. The positive electrode active material according to claim 12, wherein the size of the graphene is relative to the average particle size D of the core particles. 50 The ratio is less than 0.
1.
16. A method for preparing a positive electrode active material, the method comprising: (i) Prepare core particles comprising lithium cobalt-based composite oxides; (ii) By crushing an average size D in the range of 3 μm to 25 μm 50 Particulate graphite is prepared from flake graphite, wherein the particulate graphite has an average size D of less than 1 μm. 50 ;as well as (iii) The core particles and the microparticles are dry-mixed to obtain a positive electrode active material.
17. The method for preparing a positive electrode active material according to claim 16, wherein in the preparation of particulate graphite, the pulverization of the flake graphite is carried out for a duration of 50 minutes or more.
18. The method for preparing a positive electrode active material according to claim 16, wherein: In the preparation of particulate graphite, the flake graphite is pulverized by ball milling, and The ball milling is performed using zirconia beads with sizes ranging from 1 mm to 25 mm and at speeds ranging from 200 rpm to 5,000 rpm.
19. The method for preparing a positive electrode active material according to claim 16, wherein the particulate graphite is mixed in an amount ranging from 0.02% to 3.0% by weight based on a total of 100% by weight of the core particles and the particulate graphite.
20. The method for preparing a positive electrode active material according to claim 16, wherein: In the dry mixing process, a mixer is used to mix the core particles and the particulate graphite, and The core particles and the microparticles of graphite were measured at 1,000 s. -1 Up to 9,000 s -1 Mixing at shear rates within the range and blade rotation speeds less than or equal to 20 m / s.